Qualitative analysis of challenge- based learning on programming course / Zuraini Hanim Zaini and Easter Joseph - Zaini, Zuraini Hanim; Joseph, Easter (UiTM Cawangan Johor Kampus Pasir Gudang, 2020)
In this study, Challenge-Based learning (CBL) is implemented in Visual programming course as a mean to improve students’ programming skills. CBL provides authentic learning experience in collaborative group learning to enhance students’ deeper conceptual learning. The researchers created Oh My Code Programing Competition (OMC) to employ the CBL in the Visual Programming Course. OMC is a CBL technology apps invention project which emphasizes the innovation of the creation of an information system by instilling a business perspective in it. There are 3 main phases of CBL in OMC which consist of: 1) Challenge instructions by lecturer, 2) Preparations towards challenge 3) Delivery of complete challenge. A total of 50 students were involved in this study. The students’ reflection was gathered through an open-ended online survey. The analysis was done using Co- occurrences Analysis. In summary, the OMC in Visual programming course demonstrates that the foundation in technology can make the students successfully take on the challenge to develop a system prototype with both technical and societal component. Through this CBL, students indirectly developed various professional skills such as teamwork communication and problem solving.